Genetics of low spinal muscular atrophy carrier frequency in sub‐Saharan Africa. Issue 4 (2nd April 2014) - Sangaré, Modibo; Hendrickson, Brant; Sango, Hammadoun Ali; Chen, Kelian; Nofziger, Jonathan; Amara, Abdelbasset; Dutra, Amalia; Schindler, Alice B.; Guindo, Aldiouma; Traoré, Mahamadou; Harmison, George; Pak, Evgenia; et al.
<x xml:space="preserve">Abstract</x> Objective Spinal muscular atrophy (SMA) is one of the most common severe hereditary diseases of infancy and early childhood in North America, Europe, and Asia. SMA is usually caused by deletions of the survival motor neuron 1 (SMN1) gene. A closely related gene, SMN2, modifies the disease severity. SMA carriers have only 1 copy of SMN1 and are relatively common (1 in 30–50) in populations of European and Asian descent. SMN copy numbers and SMA carrier frequencies have not been reliably estimated in Malians and other sub‐Saharan Africans. Methods We used a quantitative polymerase chain reaction assay to determine SMN1 and SMN2 copy numbers in 628 Malians, 120 Nigerians, and 120 Kenyans. We also explored possible mechanisms for SMN1 and SMN2 copy number differences in Malians, and investigated their effects on SMN mRNA and protein levels. Results The SMA carrier frequency in Malians is 1 in 209, lower than in Eurasians. Malians and other sub‐Saharan Africans are more likely to have ≥3 copies of SMN1 than Eurasians, and more likely to lack SMN2 than Europeans. There was no evidence of gene conversion, gene locus duplication, or natural selection from malaria resistance to account for the higher SMN1 copy numbers in Malians. High SMN1 copy numbers were not associated with increased SMN mRNA or protein levels in human cell lines. Interpretation SMA carrier frequencies are much lower in sub‐Saharan Africans than in Eurasians. This finding is important to consider in SMA genetic counseling in individuals with black African ancestry. Ann Neurol 2014;75:525–532